Legacies : - Lubar, Steven (Published by Smithsonian Institution Press in association with the National Museum of American History, 2001)
This is a wonderful journey into Americana hosted by the Smithsonian. The photography is perfect, and the text is lively and informative. "Legacies" is a real potpourri of American stuff, including Judy Garland's ruby slippers from "The Wizard of Oz", Warren Harding's pajamas, inauguration gowns of several first ladies, the stove- pipe hat Lincoln wore the night he was assassinated. the original star spangled banner, Kermit the Frog, the original Teddy bear, and much much more.